Scribbling Stage Sebagai Basic Writing Step Untuk Mengembangkan Kemampuan Menulis Anak Usia Dini - Tisya Permatasari; Susijati Susijati (FKIP, Universitas Palangka Raya, 2022)
The development of writing skills in early childhood plays a significant role in preparing children for more structured writing abilities in the future. One of the initial stages in the development of writing skills in early childhood is the scribbling stage, where children make random marks and lines. The scribbling stage is often seen as a fundamental step in developing writing skills in early childhood. This literature review aims to explore the importance of the scribbling stage as a basic writing step in developing early childhood writing skills. In this study, we collected and analyzed various literature sources discussing the scribbling stage and its impact on the development of writing skills in early childhood. The findings indicate that the scribbling stage serves as a crucial foundation for developing writing skills in early childhood. During this stage, children begin to familiarize themselves with writing tools, develop creativity, gain initial understanding of writing concepts, and enhance fine motor skills. Scribbling activities also help children express their thoughts, ideas, and feelings while strengthening the coordination between the brain and hand. This research also highlights the significant implications of the scribbling stage in language development, visual perception, and problem-solving abilities in children. Support from parents and educators is crucial during the scribbling stage to establish a strong foundation for further writing development in children.